Clinical outcomes of patients undergoing Desarda versus Lichtenstein mesh for inguinal hernia repair: our experience in Qazi Hussain Ahmed Medical Complex, Nowshera Pakistan - Khan, Kamran H.; Khan, Waseem Y.; Khan, Zahid; Ghani, Fazal; Shah, Syed S. A. (International Surgery Journal, 2022)
Background: The objective of this study was to compare the outcome of Desarda versus Lichtenstein mesh for surgical repair of inguinal hernia. Methods: This randomized controlled trial was done at Qazi Hussain Ahmed Medical Complex, Nowshera from 01 February 2019 to 30 December 2020 with total duration 1 year and 10 months. Study included patients admitted in hospital for inguinal hernia repair. Patients were divided into 2 groups. Group 1 consisted of patients in whom Lichtenstein mesh repair was done while group 2 with patients having Desarda non-mesh repair done. Total time of surgery was noted. Patients were assessed for pain using a visual analog scale (VAS) after 72 hours and for seroma and infection within seven days. Recurrence and resumption of normal gait was assessed after 6 months. Data was analyzed with statistical package for the social sciences (SPSS) 21. Results: Total of 100 male patients were included in the study. About 45 patients were included in group 1 and 55 in group 2. Mean age of the patients was 53±10.55 years in Lichtenstein group and 50±08.11 years in Desarda group. The mean duration of surgery was 47.57±4.95 min with Lichtenstein while 37.96±4.76 min with Desarda. The mean pain score was 2.5±1.0 after 72 hours with Lichtenstein while 1.72±0.20 with Desarda (p<0.05). Seroma was developed in 4 (8.8%) patients, infection in 5 (11.11%) patients and recurrence occurred in 1 (2.2%) patient in group 1 (Lichtenstein) while no patient developed infection in group 2 (Desarda). The rate of normal gait observed in 6 months post operative was in 25 (55.5%) patients with Lichtenstein repair while in group 2, 30 (54.54%) patents resumed normal gate respectively (p>0.05). Conclusions: Both methods for repair are acceptable but the Desarda has less complications and operative time as compared to Lichtenstein repair.